Fundamental characteristics of material removal and surface formation in diamond turning of porous carbon. (2017) - Heidari, Mehdi; Yan, Jiwang
Porous carbon is an important material for manufacturing ultraprecision air bearings. This paper investigates the material removal mechanism and surface quality of porous carbon in diamond turning process. A total of 32 diamond turning tests were performed and the effects of feed rate, depth of cut, cutting speed, and tool rake angle were investigated. Scanning electron microscopy of the machined surface showed that three types of material removal mechanisms occurred in the diamond turning process, which was influenced by experimental conditions. Analysis of variance of experimental data demonstrated that feed rate had the most dominant effect on surface roughness, followed by depth of cut, whereas cutting speed has little effect. Tool rake angle effects material removal behaviour in a different way from that of diamond turning of other brittle materials, showing that a negative rake angle is disadvantageous. The results also indicated that by controlling the machining conditions, surface roughness, core roughness and the bearing area curve of the machined surface were controllable, and there was a 25% decrease in the percentage of porosity after machining. It was demonstrated that diamond turning can be used as an efficient method to fabricate high-precision surfaces on porous carbon for air bearing applications.